Significance of Strangeness Conservation/Violation Studies at BESIII: Study of Strangeness at BESIII - Amin, Aneela; Saeed, Khadija; Younas, Farzana; ul Islam, Ghalib (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Strangeness violation and conservation have been studied in Charmonia and its higher state decays. The data of some prominent decay modes has been collected from BESIII laboratory from the years 2009 to date. The strangeness violating decays play an important role in the study of weak interactions. On the other hand, strangeness conserving decays describe the strong interactions. An overview of strangeness conserving decays and strangeness violating decays has been given and the decay modes are presented in tabular form. The study reveals that associated production occurs only in strangeness conserving decays rather than strangeness violating decays. Experimental and theoretical results are presented in order to arrange phenomenological developments and queries may search new domains in Experimental High Energy Physics, and will explore new prospects of strangeness, a basic quantum number of hadrons and its associated production.